Alles für die Katz’?: Nochmals zum „Katzensarkophag“ des Prinzen Thutmosis - Hohneck, Heimo (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
The so-called cat’s coffin of prince Thutmose (Egyptian Museum Cairo, CG 5003), which was allegedly found during an excavation at Mit Rahina in 1892, is a curious monument. Whilst prince Thutmose is commonly regarded as a son of Amenhotep III, this coffin so far delivers the only known example for him as “eldest king’s son” and high priest of Ptah at Memphis. But, for several reasons, its authenticity seems to be very dubious.